1998
DOI: 10.1016/s0377-1237(17)30536-1
|View full text |Cite
|
Sign up to set email alerts
|

Hiv Infection in Herpes Zoster

Abstract: The interaction of Herpes zoster and Human Immunodeficiency Virus (HIV) was evaluated in 120 cases of herpes zoster admitted to our hospital and in 157 HIV positive cases detected in the hospital during the same period. The incidence of HIV seropositivity was 22.5 per cent in cases of herpes zoster without AIDS defining disease conditions. Whereas the incidence of Herpes zoster in cases detected to be HIV positive in the same period was 17.2 per cent. A large number of herpes zoster cases found to be HIV posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Study conducted by DE Sylva P et al found that majority of patients who were HIV positive was between 21 to 30 years of age. 10 Evidence like this suggest that healthy persons who develop herpes zoster and are younger than 50 years of age, should be screened for HIV. Apart from vesicular lesions, the other atypical presentations of Herpes zoster were seen in a 6 patients which includes bullous, hemorrhagic, ulcerated and crusted lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study conducted by DE Sylva P et al found that majority of patients who were HIV positive was between 21 to 30 years of age. 10 Evidence like this suggest that healthy persons who develop herpes zoster and are younger than 50 years of age, should be screened for HIV. Apart from vesicular lesions, the other atypical presentations of Herpes zoster were seen in a 6 patients which includes bullous, hemorrhagic, ulcerated and crusted lesions.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similar observations were made in our study also. Of 22 patients who developed PHN, maximum (10) developed it when treatment was initiated after 6 days while only 4(18.18 %) developed PHN when treatment was initiated within the first 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies conducted in the Armed Forces in 1991, Talwar et al [12] found involvement of trigeminal nerve in 12.18% of cases of herpes zoster, while Desylva et al in 1998 found this to be 10.75% in HIV-negative and only 7.41% in HIV-positive patients [15]. In the present study ophthalmic zoster was the presenting illness in as many as 24.6% of Herpes zoster cases, possibly indicating the future trends in its presentation as the HIV epidemic is progressing.…”
Section: Discussionmentioning
confidence: 99%